ثبات اللغة العربية في توقع حروب القيم الثقافية في عصر الثورة الصناعية 4.0 - Nurcholis, Ahmad (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2019)
The historical evidence has proved the universality of Arabic language. It is used as media of expressions in communication and literature throughout the moslem’s world. Recently, Arabics has become the blend of various cultures having been harmonized with all aspects of civilized life in the world, including in Indonesia.The existence of Arabics is getting obvious in the era of Industrial Revolution 4.0 as it attempts to anticipate a war of cultural values, especially against the West. The bottomline is that Arabics can survive and comply with other cultural influences, such as caligraphy, reciting ‘kitab kuning’ in traditional and modern pesantren, drama, carving, fine art, language, literature, philosophy, architecture, etc. The contribution of Islamic colleges are also significant. For examples; Al Azar Egypt, Ummul Qura’ Mecca as well as UIN Maulana Malik Ibrahim Malang have popularized the attribute the centre of Islamic civilization. They are well-known as the campus of civilization, tourism, and religious tolerance.